#WhiteandWoke: Racial Consciousness in White Undergraduate Students (Higher Education Politics and Economics, 2023)
This phenomenological qualitative study used White Racial Consciousness theory to conceptualize racial attitude orientation and a novel asynchronous semi-structured interview protocol to explore how White undergraduate students contextualize their experiences with diversity on campus and institutional inclusion efforts. Findings indicate that White students feel marginalized by current White privilege pedagogy approaches to diversity and inclusion and struggle to differentiate their own racial locations within Whiteness. They expressed superficial concepts about White privilege which they conflated with their own racial identity. Implications for practice and future research are provided for higher education diversity and inclusion practitioners to better engage White undergraduate students in campus diversity efforts to achieve institutional goals of inclusivity.